2017
DOI: 10.1088/1361-665x/aa9d3d
|View full text |Cite
|
Sign up to set email alerts
|

Application of magnetoelastic materials in spatiotemporally modulated phononic crystals for nonreciprocal wave propagation

Abstract: In this paper, a physical platform is proposed to change the properties of phononic crystals in space and time in order to achieve nonreciprocal wave transmission. The utilization of magnetoelastic materials in elastic phononic systems is studied. Material properties of magnetoelastic materials change significantly with an external magnetic field. This property is used to design systems with a desired wave propagation pattern. The properties of the magnetoelastic medium are changed in a traveling wave pattern,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Another way is to introduce an angular momentum bias, disobeying time-reversal symmetry as in media comprising gyroscopes or circulating fluids [5,11]. A third solution to achieve nonreciprocity is the use of dynamic materials with properties that are inhomogeneous in space and changing in time [7,[14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Another way is to introduce an angular momentum bias, disobeying time-reversal symmetry as in media comprising gyroscopes or circulating fluids [5,11]. A third solution to achieve nonreciprocity is the use of dynamic materials with properties that are inhomogeneous in space and changing in time [7,[14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches to acoustic nonreciprocity rely on breaking the spatial or temporal symmetry in the governing equations by introducing nonlinear interactions [15], [16] or spatiotemporal modulation of the properties of the medium [17], [18]. Theoretical analysis has shown that spatiotemporal modulation of strongly magnetoelastic materials, like Terfenol, and piezoelectric materials, like PZT, can lead to impressive nonreciprocity, as shown in [19]. Both nonlinearity and spatiotemporal modulation introduce secondary tones that require later demodulation or signal processing to prevent signal corruption.…”
Section: Introductionmentioning
confidence: 99%
“…The latter has been recently demonstrated in elastic metamaterials using a perturbation approach [24]. Although very challenging, several efforts have recently investigated achieving material variations in time using negative capacitance piezoelectric shunting [25], inductance-based resonance control [26], and magnetoelastic materials [27]. In this work, we build on the work developed in [28] for non-resonant space-time traveling phononic lattices to develop a mathematical framework that captures and predicts non-reciprocal dispersion physics in lumped time-traveling LRAMs.…”
Section: Introductionmentioning
confidence: 99%